2018
DOI: 10.1371/journal.pone.0199812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chewing an apple on dental plaque removal and on salivary bacterial viability

Abstract: ObjectivesStudies on dental plaque removal by chewing an apple are scarce and dated, with conflicting findings. This study aimed to determine whether chewing an apple produced mechanical removal of dental plaque or had any effect on salivary bacterial viability.MethodsThe study group consisted of 20 healthy adults with good oral health status who were randomly assigned to brush their teeth or eat an apple. After 2 weeks, the experiment was repeated with the order reversed. Plaque index (PI) and the bacterial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
11
1
1
Order By: Relevance
“…The effects of apples on oral health and bacterial control have already been examined in several studies. However, our findings contradicted the results from the study by Rubido et al However, our findings contradicted the results of a study by Rubido et al (6), in which it was found that chewing apples fail to eliminate dental plaque and in fact helped to increase the plaque (6). Possible reason is that chewing…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The effects of apples on oral health and bacterial control have already been examined in several studies. However, our findings contradicted the results from the study by Rubido et al However, our findings contradicted the results of a study by Rubido et al (6), in which it was found that chewing apples fail to eliminate dental plaque and in fact helped to increase the plaque (6). Possible reason is that chewing…”
Section: Discussioncontrasting
confidence: 98%
“…The medium toothbrush was selected since the participants were dental students and were familiar with the proper brushing technique to avoid damage to the periodontal structure. The brushing time took about 2 minutes (each quarter is 30 seconds) (6). Apple chewing was performed without any constraints; that is, participants were allowed to eat the apples with skin using both sides of their mouth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in Section 1.1 , teeth surfaces provide a permanent solid surface for bacterial colonization. Their convex surfaces protect the gingival sulcus from being fully cleaned by solid foods such as apples [ 69 ]. Bacteria also adhere to other non-shedding, solid surfaces in the oral cavity, for example, orthodontic bands, bridges, or implants [ 70 ].…”
Section: Ldc Cadaverine and Butyrate In Periodontal Health And Diseasementioning
confidence: 99%